Pengaruh Brand Image, Product Quality dan Labelisasi Halal Terhadap Keputusan Pembelian Sunblock Vaseline Healthy Di Kota Semarang - Nabila Nabila; Imam Nuryanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine and analyze the effect of brand image, product quality and halal labeling on purchasing decisions of vaseline healthy sunblock in Semarang City. Researchers determine the population, namely all consumers who use vaseline healthy sunblock products. The number of samples in this study amounted to 117 respondents through questionnaires distributed online and offline. The data collection technique uses primary data in the form of a questionnaire and uses a Likert scale in the selection of assessment responses. The analysis method used is multiple linear analysis. Based on the results obtained, it shows that the variables brand image, product quality and halal labeling have a positive and significant effect on purchasing decisions.